FAKTOR RISIKO IBU HAMIL KUNJUNGAN PERTAMA DENGAN ANEMIA DI PUSKESMAS PAJANGAN KABUPATEN BANTUL - Cahyaningtyas, Ayu; Sujiyatini, Sujiyatini; Djanah, Nur (Poltekkes Kemenkes Yogyakarta, 2016)
Millennium Development Goal (MDG's) has objective to improve maternal health where the main indicator is adecrease in maternal mortality .Hemorrhage is the cause of maternal mortality by infection with the highestpercentage , gestosis and other causes .Bleeding is one of the cause of anemia occurring in pregnant women .The prevalence of anemia in pregnant mothers in the province in 2012 which is the highest Bantul district that isequal to 28.67%. Knowledgeable description of the risk factors of pregnant women with anemia in the first visitPuskesmas Pajangan Bantul Year 2014. Descriptive research with cross sectional approach. Secondary dataMedical Record anemia in pregnant women PHC Pajangan period 1 January to 31 December 2014. The formatof data collection and Master Tabel.Risk factors pregnant women Anemia in Puskesmas Pajangan Bantul in2014, namely: age <20 years of 8.42%, 20 - 35 years 71.02% and> 35 years 20.56%, 43.93% nulliparous,multiparous grandemulti 56.07% and 0%, a distance of <2 years of 20% and % 2 years 80% .Risk factor ofAnemia in Pregnant Women PHC display of Bantul in 2014 the majority of the age of 20-35 years old,multiparous and a distance of >2years.